Odpowiedzi

  • Roma
  • Community Manager
2010-01-24T10:04:23+01:00
( 3(2x-1) +4(y-2) =9
( 2(5x-1) +3y = 5(3x+y) + 2

( 6x - 3 + 4y - 8 = 9
( 10x - 2 + 3y = 15x + 5y + 2

( 6x + 4y = 9 + 3 + 8
( 10x - 15x + 3y - 5y = 2 + 2

( 6x + 4y = 20 /:2
( - 5x - 2y = 4

( 3x + 2y = 10
( - 5x - 2y = 4
_______________
-2x = 14 /:(-2)
x = -7

3x + 2y = 10
3*(-7) + 2y = 10
-21 + 2y = 10
2y = 10 + 21
2y = 31 /:2
y = 15,5

( x = -7
( y = 15,5
1 5 1
2010-01-24T10:44:32+01:00
3(2x-1) +4(y-2) =9
2(5x-1) +3y = 5(3x+y) + 2

6x - 3 + 4y - 8 = 9
10x - 2 + 3y = 15x + 5y + 2

6x + 4y = 9 + 3 + 8
10x - 15x + 3y - 5y = 2 + 2

6x + 4y = 20 /:2
- 5x - 2y = 4

3x + 2y = 10
- 5x - 2y = 4
_____________
-2x = 14 /:(-2)
x = -7

3x + 2y = 10
3*(-7) + 2y = 10
-21 + 2y = 10
2y = 10 + 21
2y = 31 /:2
y = 15,5

x = -7
y = 15,5